J DO FEMALE CARRIERS OF THE ABCD1 GENE FOR X-LINKED ADRENOLEUKODYSTROPHY MANIFEST WITH URINARY SYMPTOMS?. (29th November 2012) - Hofereiter, A; Smith, M; Seth, J; Fox, Z; Murphy, E; Emmanuel, A; Lachmann, R; Panicker, J
Abstract : Introduction: Adrenoleukodystrophy (ALD) is caused by a defective copy of the X-linked ABCD1 gene. Adrenomyeloneuropathy (AMN) represents a mild and later-onset phenotype of the spectrum of ALD. Bladder and bowel dysfunction have been described in men with AMN, however their occurrence in female heterozygotes (carriers) is unclear. We documented the prevalence and severity of bladder and bowel symptoms in a large cohort using standard questionnaires. Methods: In this prospective survey, 48 patients with confirmed mutation of the ABCD1 gene (29 females, mean age 47) were contacted for consent and sent questionnaires International Prostate Symptom Score (IPSS), Urinary Symptom Profile (USP), SF-Qualiveen and the neurogenic bowel dysfunction (NBD) score. The overactive bladder (OAB) subscore (part of USP) was compared to a cohort of 17 women with multiple sclerosis (MS). Results: All males and 20 females (68.9%) reported urinary symptoms. The IPSS mean score was 16 for males and 9 for females, with 31% of men and 14% of women having severe symptoms. Interestingly, there was no significant difference in the overactive bladder (OAB) subscore between females and males (p=0.35). Furthermore, when OAB subscores of females were compared to that of another cohort, females with MS (n=17), there was no significant difference between scores (p=0.27). 21% of males and 10% of females had moderate to severe bowel dysfunction. Conclusion: Bladder and bowel complaints are common amongst patients with AMN. Female heterozygotes, who are considered to be only carriers, can indeed experience bladder symptoms as severe as in males, and symptoms are comparable to that experienced in other neurological conditions.